Structural, magnetic, thermal, biocompatibility, and electronic properties of lanthanum doped-magnesium hydroxyapatite - Mahmood, Bahroz Kareem; Kareem, Rebaz Obaid; Bulut, Niyazi; Ates, Tankut; Keser, Serhat; Kaygili, Omer; Kurucay, Ali (Elsevier Sci Ltd, 2025)
This study presents the preliminary experimental and theoretical results on Mg/La co-substituted in hydroxyapatite (HAp) structure. Four Mg-based HAps were synthesized with La doping by keeping the Mg concentration constant at 0.45 at.%, while the La content was varied from 0.45 to 1.80 at.% in 0.45 at.% increments by a wet chemical method. Experimentally, the major phase for all samples was HAp and the minor phase was beta-TCP. The presence of La as a dopant for the HAp structure was found to affect the lattice parameters. The values of lattice parameters and unit cell volume were observed to increase gradually. The crystallinity percentage ranged from 85 % to 89 %. Analysis using the Scherrer and Williamson-Hall approaches revealed that the crystallite size values of the samples were in the range of 22-29 nm and 23-33 nm respectively. In addition, the values of lattice stress, strain and anisotropic energy density were influenced by the concentration of La. The magnetic saturation decreased from 0.0439 to 0.0383 emu/g with an increase in the amount of La. All samples showed biocompatible properties. A slight change in morphology was also observed. The EDX results showed that the presence of La at different levels resulted in calcium deficiency. Thermogravimetric analysis and differential thermal analysis, carried out over a temperature range of 25-850 degrees C, showed that each sample had thermal stability, with no exothermic or endothermic peaks detected. Theoretical results derived from Density Functional Theory (DFT) calculations showed that the band gap values decreased steadily from 4.578 to 4.438 eV.
Keywords: Hydroxyapatite; Lanthanum (La); Magnesium (Mg); Band structure; X-ray diffraction (XRD)